Mechanical impact of parturition‐related strains on rat pelvic striated sphincters. Issue 3 (19th February 2019) - Duran, Pamela; Ward, Samuel; Christman, Karen L.; Alperin, Marianna
Abstract: Aims: To define the operational resting sarcomere length (Ls ) of the female rat external urethral sphincter (EUS) and external anal sphincter (EAS) and to determine the mechanism of parturition‐related injury of EUS and EAS using a simulated birth injury (SBI) vaginal distention model. Methods: EUS and EAS of 3‐month‐old Sprague‐Dawley control and injured rats were fixed in situ, harvested, and microdissected for Ls measurements and assessment of ultrastructure. EUS and EAS function was determined at baseline, and immediately and 4 weeks after SBI, using leak point pressure (LPP) and anorectal manometry (ARM), respectively. Operational L s was compared to species‐specific optimal L s using one sample Student's t test. Data (mean ± SD) were compared between groups and time points using repeated measures one‐way analysis of variance, followed by Tukey's post hoc pairwise comparisons, with significance set to 0.05. Results: The operational resting Ls of both sphincters (EUS: 2.09 ± 0.07 µm, EAS: 2.02 ± 0.03 µm) was significantly shorter than optimal rat Ls of 2.4 µm. Strains imposed on EUS and EAS during SBI resulted in significant sarcomere elongation and disruption, compared with the controls (EUS: 3.09 ± 0.11 µm, EAS: 3.37 ± 0.09 µm). Paralleling structural changes, LPP and ARM measures were significantly lower immediately (LPP: 21.5 ± 1.0 cmH2 O, ARM: 5.1 ± 2.31 cmH2 O) and 4 weeks (LPP: 27.7 ± 1.3cmH2 O, ARM: 2.5 ± 1.0 cmH2 O) after SBI relative to the baseline (LPP: 43.4 ± 8.5 cmH2 O, ARM: 8.2 ± 2.0 cmH2 O); P  < 0.05. Conclusions: Analogous to humans, the short resting Ls of rat EUS and EAS favors their sphincteric function. The insult experienced by these muscles during parturition leads to sarcomere hyperelongation, myofibrillar disruption, and dysfunction of the sphincters long‐term.